Мовне вираження концепту Бог у поетичному просторі Віктора Бойка (за матеріалами збірки "Планида") - Черненко, Ольга Ігорівна (Донецький національний університет ім. Василя Стуса, 2020)
У статті висвітлено особливості мовної репрезентації концепту БОГ у поетичному ідіостилі В. С. Бойка. Аналіз концепту БОГ відіграє важливу роль при дослідженні духовних цінностей українського народу крізь призму самобутнього ментального коду за допомогою здобутків лінгвокогнітивних і лінгвокультурологічних учень. Складники аналізованого концепту є варіативними й становлять значний пласт для дослідження. Статтю присвячено видатному харківському письменнику й поету другої половини ХХ століття – В. С. Бойку. Указано, що у своїх творчих пошуках майстер слова часто звертається до концепту БОГ й експлікує низку смислових наповнень. При цьому визначено, які мовні засоби добирає митець для актуалізації у свідомості реципієнтів того чи іншого художньо-смислового наповнення. Проілюстровано ставлення поета до Бога й віри, еволюцію душевного й емоційного станів його свідомості.

The research of the article highlights the peculiarities of the linguistic represen-tation of the concept of GOD in the poetic individual style of V. S. Boyko. The spiritual state of a person plays an important role in his or her socialization in society. Whatever country in the world is concerned, it is obvious that religion is affecting the lives of millions of people. The concept of GOD exists in the intangible, inner world of the individual, affecting his emotional state. The con-cept of GOD belongs to the universal, because it is included in the linguistic picture of the world of any ethnos. It can be considered as a key to understanding the moral values of both the whole ethnos and the individual. This concept is also important in poetic speech, especially when it comes to a writer whose work is thoroughly imbued with emotion and deep psychology. The purpose of the analysis is to show the concept of GOD what plays an important role in the study of the moral values of the Ukrainian people through the prism of the original men-tal code through the achievements of linguocognitive and linguocultural studies. The components of the concept analyzed are variable and constitute a significant layer for research. The article is devoted to the outstanding Kharkov writer of the second half of the twentieth century – V. S. Boyko. It is stated that in his creative pursuits the master of words often resorts to the concept of GOD and explicates a number of semantic contents. For example, within the semantic plan of the god-supernatural being, the following semantic contents are distinguished: god-justice, god-help, god-love, god-forgiveness. The theory of the concept GOD determines what language means the writer se-lects for actualization in the mind of the recipients of a particular artistic and semantic content. The poet’s attitude to GOD and faith, the evolution of the mental and emotional states of his conscious-ness, are illustrated.
Language expressions of the concept god in Viktor Boyko’s poetic world
Keywords: художньо-семантична площина; художньо-семантичне наповнення; епітет; ідіостиль; semantic plan; semantic content; metaphor; epithet; individual style